1983
DOI: 10.1055/s-2007-969896
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Essential Oil ofCommiphora guidotti

Abstract: From the essential oil of Commiphora guidotti seven sesquiterpene hydrocarbons and a furanosesquiterpenoid, furanodiene, were isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…1 clarified that the botanical origin of opopanax, also known as scented myrrh ('bissabol', Hindi or 'habak hadi', Somali) is C. guidottii, a species found in abundance in eastern Ethiopia and Somalia. 13 In a previous study 14 of the essential oil of the resin of C. guidottii, α-santalene, α-bisabolene and furanodiene were found to be the most abundant components. In this study, as shown in Table 2, a total of 23 components were identified from the oil of opopanax with (E)-β-ocimene (33.0%) and sesquiterpene hydrocarbons, cis-α-bisabolene (22.2%) and α-santalene (15.8%) as the major components.…”
Section: Resultsmentioning
confidence: 91%
“…1 clarified that the botanical origin of opopanax, also known as scented myrrh ('bissabol', Hindi or 'habak hadi', Somali) is C. guidottii, a species found in abundance in eastern Ethiopia and Somalia. 13 In a previous study 14 of the essential oil of the resin of C. guidottii, α-santalene, α-bisabolene and furanodiene were found to be the most abundant components. In this study, as shown in Table 2, a total of 23 components were identified from the oil of opopanax with (E)-β-ocimene (33.0%) and sesquiterpene hydrocarbons, cis-α-bisabolene (22.2%) and α-santalene (15.8%) as the major components.…”
Section: Resultsmentioning
confidence: 91%
“…Major constituents of C. myrrha (furanodiene, 19AE7%; furanoeudesma-1,3-diene, 34AE0%; and lindestrene, 12AE0%) have previously been reported from an Ethiopian species (Hanuš et al 2005). An earlier study conducted by Craveiro et al (1983) 2003;Camarda et al 2007), demonstrated compositional congruency of these Ethiopian-derived oils. Previous antimicrobial studies on C. myrrha oleo-gum resin using ethanol and ether solvents for extraction have been tested with poor activity (MIC values ranging from 10 to 40 mg ml )1 ) (Omer et al 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Many papers have described the GC analysis of volatile oil from different Commiphora species, covering C. myrrha (Dekebo et al, 2002a;MortezaSemnani and Saeedi, 2003), C. guidottii (Craveiro et al, 1983), C. quadricincta (Assad et al, 1997), C. holtziana (Provan et al, 1987;Dekebo et al, 2002a), C. sphaerocarpa and C. kataf (Dekebo et al, 2002a). Monoterpenoids including a-pinene, camphene, b-pinene, myrcene and limonene have been detected.…”
Section: Monoterpenoids Sesquiterpenoids and Volatile Oilmentioning
confidence: 99%